2004
DOI: 10.1103/physrevb.70.085304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an interface dipole layer on molecular level alignment at an organic-conductor interface studied by ultraviolet photoemission spectroscopy

Abstract: The effect of an interface dipole layer on the energy level alignment at organic-conductor interfaces is studied on a copper phthalocyanine (CuPc) monolayer/electric dipole layer/graphite system via ultraviolet photoemission spectroscopy (UPS) and metastable atom electron spectroscopy. An oriented monolayer of the OTi-phthalocyanine molecule, which has an electric dipole moment, is grown on graphite to yield a welldefined dipole layer with the vacuum side negatively charged. The CuPc monolayer is sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
143
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 39 publications
(81 reference statements)
13
143
0
Order By: Relevance
“…For CuPc deposited on Au [23] (Figure 4a), we found qualitative agreement with prior photoemission [8,[22][23][24][25] and inverse photoemission [23,26] experimental data. The positions of the band edges, as determined by photoemission and inverse photoemission at room temperature, do not directly demonstrate that CuPc is strongly more p-type relative to P(VDF-TrFE).…”
Section: Interface Dipole Alignmentsupporting
confidence: 76%
See 3 more Smart Citations
“…For CuPc deposited on Au [23] (Figure 4a), we found qualitative agreement with prior photoemission [8,[22][23][24][25] and inverse photoemission [23,26] experimental data. The positions of the band edges, as determined by photoemission and inverse photoemission at room temperature, do not directly demonstrate that CuPc is strongly more p-type relative to P(VDF-TrFE).…”
Section: Interface Dipole Alignmentsupporting
confidence: 76%
“…Although copper phthalocyanine is considered a planar molecule with no permanent electric dipole [22], the molecular orbital alignment of adsorbed copper phthalocyanine is affected by both interface dipoles [8,13] and molecular orientation [13,22] while interactions or charge transfer influence the highest occupied (HOMO) to lowest unoccupied (LUMO) gap [23]. Indeed, with adsorption on metallic substrates copper phthalocyanine exhibits an electric dipole as the molecular center copper atom is not in the same plane as the surrounding ligand, and adopts a position that is typically closer to the interface [27].…”
Section: Some Background On the Organic Semiconductors Comparedmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies using ultraviolet photoelectron spectroscopy ͑UPS͒ have been performed to clarify the ELA mechanism on weakly interacting organic interfaces, and have shown that the vacuum level ͑VL͒ misalignment and drastic variation of the Fermi level ͑E F ͒ in the organic band gap appear in various organic interface systems. [1][2][3][4][5][6][7][8] Because thermal equilibrium concept strictly requires that the Fermi levels of the organic film and the electrode coincide at the interface after contact, our understanding of the ELA mechanism still lacks consistency with this requirement. 5,6 The mystery on the ELA mechanism must be related to the density of gap states ͑DOGS͒ to control the E F .…”
mentioning
confidence: 99%